Hydrogenated diene polymer, veil, rubber composition, and tire
Patent Information
- Application Number
- JP2022568097
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-12-08
- Filing Date
- 2021-10-26
- Publication Date
- 2025-03-03
- Estimated Expiration
- 2041-10-26
AI Technical Summary
【0012】 本発明によれば、低温性能と耐摩耗性に優れ、かつ破断強度に優れた加硫物が得られるゴム組成物に用いる水添ジエン重合体を提供できる。
Smart Images

Figure 0007638301000001 
Figure 0007638301000002 
Figure 0007638301000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a hydrogenated diene polymer, a veil, a rubber composition, and a tire. [Background technology]
[0002] In recent years, all-season tires have become increasingly popular, and there is a strong demand for improved low-temperature performance of tires. Conventionally, methods proposed for improving the low-temperature performance of tires include adding a rubber material with a low glass transition temperature, such as high-cis polybutadiene rubber or natural rubber, to a rubber composition for tires, or adding oil as a plasticizer, in order to reduce the elastic modulus at low temperatures and ensure high conformability of the tread rubber to the road surface at low temperatures. However, such a method has a problem in that it reduces the breaking strength of the rubber composition.
[0003] In view of such problems, a method of adding liquid rubber as a plasticizer to a rubber composition has been proposed as a method for improving low-temperature performance while maintaining the breaking strength of the rubber composition (see Patent Document 1). Because liquid rubber has unsaturated bonds, they bond during vulcanization, thereby improving the breaking strength of the rubber composition. However, the addition of liquid rubber to the rubber composition reduces the viscosity and deteriorates the abrasion resistance, which is a problem.
[0004] In recent years, in the field of rubber compositions for tire treads, sheets, films, and asphalt modification, rubber compositions containing rubber-like polymers having an ethylene structure and into which crosslinkable unsaturated groups have been introduced have been proposed for the purpose of increasing mechanical strength and compression set. By containing such rubber-like polymers, the breaking strength of the rubber composition is improved, and the wear resistance of tires is also improved (for example, see Patent Documents 1 to 5). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2008-50432 A [Patent Document 2] International Publication No. 2003 / 085010 [Patent Document 3] International Publication No. 2019 / 151126 [Patent Document 4] International Publication No. 2019 / 151127 [Patent Document 5] International Publication No. 2019 / 078083 Summary of the Invention [Problem to be solved by the invention]
[0006] However, the rubber-like polymers proposed so far, which have an ethylene structure and have crosslinkable unsaturated groups introduced therein, tend to have poor processability and reduce the dispersibility of the silica-based filler in the rubber composition, which tends to impair the fuel economy of the rubber composition.
[0007] In view of the above-mentioned problems in the prior art, an object of the present invention is to provide a hydrogenated diene polymer for use in a rubber composition which can give a vulcanizate having excellent low-temperature performance and abrasion resistance as well as excellent breaking strength. [Means for solving the problem]
[0008] Means for Solving the Problems of the Prior Art The present inventors have conducted intensive studies to solve the problems of the prior art as described above, and as a result have found that by setting the degree of branching of the hydrogenated diene polymer used in the rubber composition, the composition ratio of the structural units of the polymer, and the hydrogenation rate within specific ranges, a rubber composition which, when vulcanized, has excellent low-temperature performance, abrasion resistance, and breaking strength can be obtained, and have thus completed the present invention. That is, the present invention is as follows.
[0009] [1] The branching degree (Bn) measured by a GPC-light scattering measurement method with a viscometer is 1.5 or more. When the constituent ratios (mol%) of the structural unit represented by the following formula (1), the structural unit represented by the following formula (2), the structural unit represented by the following formula (3), and the structural unit represented by the following formula (4) are a, b, c, and d, respectively: Satisfy the following formula (S), The hydrogenation rate is 40-85%. Contains a nitrogen atom, The modification rate is 70% by mass or more, The content of aromatic vinyl monomer units is 0.1% by mass or less. Hydrogenated diene polymer. Formula (S): 10≦[(a+b) / (a+b+c+d)]×100≦70
[0010] [ka]
[0011] [2] The branching degree (Bn) measured by a GPC-light scattering measurement method with a viscometer is 1.5 or more. Satisfy the following formula (S), The hydrogenation rate is 40-80%. The hydrogenated diene polymer according to [1] above. Formula (S): 10≦[(a+b) / (a+b+c+d)]×100≦60 [3] The hydrogenated diene polymer according to the above [1] or [2], wherein the following formula (X) is 2.0 or less: Formula(X):(a+c) / (a+b) [4] The hydrogenated diene polymer according to [3] above, wherein the formula (X) is 0.8 or more and 2.0 or less. [5] The hydrogenated diene polymer according to any one of [1] to [4] above, having a hydrogenation rate of 51% or more. [6] The hydrogenated diene polymer according to any one of [1] to [5] above, having a hydrogenation rate of 71% or less. 〔7〕 The aluminum content is less than 2 ppm. 〔6〕 2. The hydrogenated diene polymer according to claim 1 . 〔8〕 The above [1] to 〔7〕 2. A veil which is a molded product of the hydrogenated diene polymer according to claim 1. 〔9〕 The above [1] to 〔7〕 100 parts by mass of a rubber component comprising 10 parts by mass or more and 50 parts by mass or less of the hydrogenated diene polymer according to any one of the above items and 50 parts by mass or more and 90 parts by mass or less of a diene rubber; A silica-based inorganic filler is 20 parts by mass or more and 100 parts by mass or less, Contains Rubber composition. 〔10〕 The liquid rubber is contained in an amount of 2 parts by mass or more and 25 parts by mass or less. 〔9〕 The rubber composition according to claim 1. 〔11〕 The above 〔10〕 A tire which is a molded article of the rubber composition according to claim 1. Effect of the Invention
[0012] According to the present invention, there can be provided a hydrogenated diene polymer for use in a rubber composition which gives a vulcanizate having excellent low-temperature performance, abrasion resistance and breaking strength. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, an embodiment of the present invention (hereinafter, referred to as "the present embodiment") will be described in detail. It should be noted that the following embodiment is merely an example for explaining the present invention, and the present invention is not limited to the following embodiment. The present invention can be practiced with appropriate modifications within the scope of the gist of the present invention.
[0014] [Hydrogenated diene polymer] The hydrogenated diene polymer of the present embodiment is The degree of branching (Bn) measured by a GPC-light scattering measurement method with a viscosity detector is 1.5 or more, and when the constituent ratios (mol%) of the structural unit represented by the following formula (1), the structural unit represented by the following formula (2), the structural unit represented by the following formula (3), and the structural unit represented by the following formula (4) are a, b, c, and d, respectively, the following formula (S) is satisfied and the hydrogenation rate is 40 to 85%. Formula (S): 10≦[(a+b) / (a+b+c+d)]×100≦70
[0015] [ka]
[0016] The hydrogenated diene polymer of the present embodiment contains conjugated diene monomer units and, if necessary, other monomer units as constituent monomer units. The hydrogenated diene polymer of this embodiment is characterized in that it is substantially free of aromatic vinyl monomer units as monomer units constituting the polymer. The term "substantially free" means that "aromatic vinyl compounds" are not used as polymerization monomers. Strictly speaking, it does not mean that the content is completely zero, taking into consideration cases where the aromatic vinyl compounds are contained as impurities, but for example, when the structure of the polymer is analyzed by NMR, the content is less than the lower limit of the value that can be normally detected when the aromatic vinyl compound is used as a polymerization monomer.
[0017] The hydrogenated diene polymer of the present embodiment is preferably one having a structure containing an ethylene structure and a conjugated diene monomer unit by (co)polymerizing a conjugated diene monomer and then hydrogenating a portion of the conjugated diene monomer unit.
[0018] As described above, the hydrogenated diene polymer of the present embodiment is substantially free of structural units derived from aromatic vinyl compounds (hereinafter also referred to as "aromatic vinyl monomer units"), which can improve low-temperature performance when a rubber composition using the hydrogenated diene polymer of the present embodiment is vulcanized. From this viewpoint, in this specification, "substantially free" means that the aromatic vinyl monomer unit is not contained at a level that affects the low-temperature performance of the conjugated diene polymer. Specifically, since the content of the aromatic vinyl monomer unit tends to affect the low-temperature performance of the vulcanizate, it is preferable to suppress the content of the aromatic vinyl monomer unit to such an extent that the effect on this is 5% or less. Specifically, the concentration is preferably 0.1% by mass or less with respect to the total mass of the hydrogenated diene polymer of this embodiment. For example, since styrene and the like are likely to affect the fuel economy performance when a rubber composition using the hydrogenated diene polymer of this embodiment is vulcanized, the styrene content in the hydrogenated diene polymer of this embodiment is preferably 0.1 mass% or less. It is also preferable that monomer units derived from other monomers than the aromatic vinyl monomer units are not contained at a level that would affect the low-temperature performance of the vulcanizate using the hydrogenated diene polymer of this embodiment.
[0019] Low temperature performance correlates with the low elastic modulus of the rubber composition in a low temperature environment. The hydrogenated diene polymer of the present embodiment does not substantially contain aromatic vinyl monomer units, and therefore has a lower glass transition temperature and excellent low temperature performance compared to SBR. In addition, the constituent ratio a of the structural unit represented by the formula (1) formed in the diene polymer by hydrogenation contributes to a decrease in elastic modulus at low temperatures. From this viewpoint, the hydrogenation rate of the hydrogenated diene polymer of the present embodiment is 40 to 85%, and satisfies the formula (S): 10≦[(a+b) / (a+b+c+d)]×100≦70. Preferably, the hydrogenation rate is 40 to 75%, and satisfies the formula (S): 40≦[(a+b) / (a+b+c+d)]×100≦70. More preferably, the hydrogenation rate is 40 to 60%, and satisfies the formula (S): 50≦[(a+b) / (a+b+c+d)]×100≦70. By setting the hydrogenation rate and formula (S) in the above-mentioned ranges for the hydrogenated diene polymer of the present embodiment, the structural unit represented by formula (1) is sufficiently present in the hydrogenated diene polymer, the constituent ratio a becomes a sufficient value, and the rubber composition containing the hydrogenated diene polymer has excellent low-temperature performance.
[0020] In this specification, the term "monomer" refers to a compound before polymerization, and the term "monomer unit" refers to a structural unit that constitutes a polymer. The "ethylene structure" includes both those generated by hydrogenating a portion of the double bond portion of a conjugated diene monomer unit and ethylene monomer units in the case where ethylene is used as a monomer.
[0021] The hydrogenated diene polymer of this embodiment can be produced by polymerizing a conjugated diene monomer and, if necessary, other monomers, followed by hydrogenation. As a specific method, for example, as described in WO 96 / 05250, JP 2000-053706, WO 2003 / 085010, WO 2019 / 151126, WO 2019 / 151127, WO 2002 / 002663, and WO 2015 / 006179, it is preferable to produce by a method in which a conjugated diene monomer is polymerized by anionic polymerization under various additives and conditions, and then copolymerized with other monomers as necessary and then hydrogenated.
[0022] Conjugated diene monomers include, but are not limited to, 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, 3-methyl-1,3-pentadiene, 1,3-hexadiene, and 1,3-heptadiene. Among these, from the viewpoint of industrial availability, 1,3-butadiene and isoprene are preferred, and 1,3-butadiene is more preferred. These may be used alone or in combination of two or more.
[0023] In addition, the other monomers include, but are not limited to, non-conjugated polyene compound monomers such as ethylidene norbornene, dicyclopentadiene, and vinyl norbornene; and cyclic non-conjugated polyene compound monomers such as dicyclopentadiene, vinyl norbornene, and ethylidene norbornene. By using such other monomers, the balance of breaking strength, fuel economy, wet skid resistance, and abrasion resistance tends to be improved when used in vulcanized products, especially tires. These may be used alone or in combination of two or more.
[0024] (Hydrogenation rate) The hydrogenated diene polymer of this embodiment has a hydrogenation rate of 40% or more, preferably 45% or more, more preferably 51% or more, and even more preferably 55% or more. A hydrogenation rate of 40% or more increases the ethylene structure and reduces the molecular weight between entanglement points of molecular chains, i.e., the minimum molecular weight of one molecular chain required for one molecular chain to be entangled with another molecular chain at one point. This increases the number of entanglements of molecular chains, and tends to further improve the breaking strength when vulcanized. On the other hand, the hydrogenation rate of the hydrogenated diene polymer of this embodiment is 85% or less, preferably 80% or less, more preferably 75% or less, more preferably 71% or less, and even more preferably 65% or less. A hydrogenation rate of 85% or less improves the ease of crosslinking, and the hysteresis loss is reduced by eliminating microcrystals derived from the ethylene structure, which tends to further improve fuel efficiency when vulcanized. The hydrogenation rate is shown in the examples. 1 It can be calculated using a technique using H-NMR. The hydrogenation rate of the hydrogenated diene polymer of the present embodiment can be controlled within the above numerical range by adjusting the amount of double bonds contained in the conjugated diene monomer units.
[0025] (Degree of branching) From the viewpoint of suppressing cold flow when made into a rubber bale and improving processability, represented by ease of kneading with a filler or a crosslinking agent, the hydrogenated diene polymer of the present embodiment has a branching degree (Bn) measured by a GPC-light scattering measurement method with a viscosity detector (hereinafter also simply referred to as "branching degree (Bn)") of 1.5 or more, preferably 3.0 or more, and more preferably 4.0 or more. The branching degree (Bn) represents the number of polymer chains attached to the longest polymer backbone. For example, the degree of branching (Bn) being 2 or more means that the hydrogenated diene polymer of the present embodiment substantially has two or more side polymer chains relative to the longest polymer main chain.
[0026] The branching degree (Bn) of the hydrogenated diene polymer of the present embodiment is defined as g'=6Bn / {(Bn+1)(Bn+2)}, using the shrinkage factor (g') measured by a GPC-light scattering method with a viscosity detector. In general, a polymer having branches tends to have a smaller molecular size when compared to a linear polymer having the same absolute molecular weight. The shrinkage factor (g') is a measure of the ratio of the molecular size to that of a linear polymer of the same assumed absolute molecular weight. In other words, the greater the degree of branching of a polymer, the smaller the shrinkage factor (g') tends to be. In the hydrogenated diene polymer of the present embodiment, the intrinsic viscosity is used as an index of molecular size for this shrinkage factor. 0.771 In the above formula, M is the absolute molecular weight. However, the shrinkage factor represents the rate of reduction in molecular size and does not accurately represent the branched structure of a polymer. Therefore, the branching degree (Bn) of the hydrogenated diene polymer is calculated using the value of the shrinkage factor (g') at each absolute molecular weight of the hydrogenated diene polymer. The calculated "branching degree (Bn)" accurately represents the number of polymers directly or indirectly bonded to each other with respect to the longest main chain structure. The calculated branching degree (Bn) is an index expressing the branched structure of the hydrogenated diene polymer. For example, in the case of a typical four-branched star polymer (four polymer chains connected to a central part), two polymer chain arms are attached to the longest highly branched main chain structure, and the branching degree (Bn) is evaluated as 2. In a typical eight-branched star polymer, six polymer chain arms are attached to the longest highly branched main chain structure, and the branching degree (Bn) is evaluated as six. Here, "branch" refers to a structure formed by direct or indirect bonding of one polymer to another polymer, and "degree of branching (Bn)" refers to the number of polymers that are directly or indirectly bonded to each other in the longest main chain structure. The hydrogenated diene polymer of the present embodiment has a degree of branching (Bn) of 1.5 or more, and therefore can suppress cold flow when made into a rubber bale, has extremely excellent processability (workability) when made into a vulcanizate, and has excellent breaking strength and breaking elongation when made into a vulcanizate. From the same viewpoint, the hydrogenated diene polymer of this embodiment preferably has a branching degree (Bn) of 3.0 or more, more preferably 4.0 or more. The upper limit of the branching degree (Bn) is not particularly limited and may be equal to or higher than the detection limit, but is preferably 84 or less, more preferably 80 or less, even more preferably 64 or less, and even more preferably 57 or less. The hydrogenated diene polymer of this embodiment has a degree of branching (Bn) of 84 or less, and therefore tends to have excellent breaking strength and breaking elongation when vulcanized.
[0027] (Formula (S)) The hydrogenated diene polymer of the present embodiment satisfies the following mathematical formula (S) when the constituent ratios (mol %) of the structural unit represented by the following formula (1), the structural unit represented by the following formula (2), the structural unit represented by the following formula (3), and the structural unit represented by the following formula (4) are a, b, c, and d, respectively. Formula (S): 10≦[(a+b) / (a+b+c+d)]×100≦70 The ratios of a, b, c, and d can be controlled by adjusting the type and amount of polar compound, polymerization temperature, and amount of hydrogen to be reacted when polymerizing the polymer before hydrogenation.
[0028] [ka]
[0029] The above formula (S) represents the molar ratio (mol %) of 1,2-vinyl bonds and hydrogenated 1,2-vinyl bonds in the hydrogenated diene polymer. In the hydrogenated diene polymer of this embodiment, from the viewpoint of improving the wet skid resistance, the above formula (S) is 10 mol % or more, more preferably 15 mol % or more, and further preferably 20 mol % or more. Furthermore, from the viewpoint of improving wear resistance, the above formula (S) is 70 mol % or less, preferably 60 mol % or less, more preferably 40 mol % or less, and even more preferably 30 mol % or less. The method of controlling the formula (S) within the above range includes adjusting the polymerization temperature and adding a polar compound. For example, adding 0.1 molar equivalent of a polar compound per mole of the organolithium compound can increase the 1,2-bond by about 2%.
[0030] Incidentally, (a+c) / (a+b+c+d) calculated from the above a, b, c, and d represents the above-mentioned hydrogenation rate. When a conjugated diene polymer consisting of a structural unit represented by the formula (2) and a structural unit represented by the formula (4) is hydrogenated, the structural unit represented by the formula (2) reacts preferentially to become the structural unit represented by the formula (1). In the case of the hydrogenation reaction shown in this embodiment, when the total amount of the structural units represented by the formula (2) is taken as 100 mol%, after 80 to 90 mol% are hydrogenated to become the structural unit represented by the formula (1), the reaction of the structural unit represented by the formula (4) tends to start.
[0031] The method for measuring the above formula (S) resulting from the butadiene bond units contained in the hydrogenated diene polymer of this embodiment is not particularly limited, and it can be measured, for example, by the method described in the Examples below.
[0032] (Formula(X)) In the hydrogenated diene polymer of the present embodiment, when the constituent ratios (mol %) of the structural units represented by the formulas (1) to (4) are a, b, c, and d, respectively, the following mathematical formula (X) using a, b, c, and d is defined as follows: Formula (X)=(a+c) / (a+b) The formula (X) represents the linearity in the hydrogenated diene polymer, that is, the ratio of repeating units having low linearity to hydrogenated repeating units.
[0033] When the ratio of b and a, which are 1,2-vinyl bonds and hydrogenated 1,2-vinyl bonds, is low, the linearity of the molecule increases, the denominator becomes smaller, and the formula (X) becomes larger. Since a affects both the numerator and the denominator, the size of c tends to contribute to the size of the molecule, and the larger c, which is the constituent ratio of the structural unit in formula (3), the higher the tendency to express crystallinity derived from the ethylene structural chain. The crystalline structure rapidly increases the elastic modulus of the diene polymer, making the rubber harder. The present inventors considered that the formula (X) reflects the structure of the hydrogenated diene polymer and shows the above-mentioned properties, and as a result of investigating the relationship between specific values and the properties of the hydrogenated diene polymer using specific hydrogenated diene polymers, they found the following tendency. That is, the formula (X) is preferably 2.0 or less, more preferably 1.8 or less, and further preferably 1.6 or less. When the formula (X) is 2.0 or less, it is possible to suppress the hydrogenated diene polymer from generating crystals derived from ethylene structural chains, and it is possible to avoid a rapid increase in the elastic modulus. As a result, the hydrogenated diene polymer of the present embodiment does not become too hard, and the veil made of the hydrogenated diene polymer has excellent moldability. The formability of the veil can be measured by the method described in the Examples below.
[0034] The formula (X) of the hydrogenated diene polymer of this embodiment is preferably 0.8 or more, more preferably 1.0 or more, and even more preferably 1.2 or more. When the formula (X) is 0.8 or more, the structure of the hydrogenated diene polymer satisfies a=32, b=8, c=0, and d=60, although this is only an example. In the hydrogenated diene polymer of this embodiment, b is preferentially hydrogenated in a state in which b and d coexist. Therefore, by making the formula (X) 0.8 or more, the proportion of b, which is a reactive unsaturated group, in the hydrogenated diene polymer can be made 8% or less, and the thermal stability of the hydrogenated diene polymer can be improved. As a result, gelation is less likely to occur during kneading of a rubber composition using the hydrogenated diene polymer of this embodiment. The formula (X) can be controlled within the above-mentioned numerical range by adjusting the type and amount of the polar compound, the polymerization temperature, and the amount of hydrogen to be reacted when polymerizing the polymer before hydrogenation.
[0035] (denaturation rate) The hydrogenated diene polymer of the present embodiment preferably contains a nitrogen atom from the viewpoint of improving fuel economy when vulcanized. Nitrogen atoms can be introduced using a modifier, which tends to improve the dispersibility of the silica-based inorganic filler, which is a reinforcing material for tires.
[0036] From the viewpoint of dispersibility of the silica-based inorganic filler that is a tire reinforcing material, the hydrogenated diene polymer of the present embodiment preferably has a modification rate of 65 mass % or more, more preferably 70 mass % or more, and even more preferably 75 mass % or more. The hydrogenated diene polymer of the present embodiment is not particularly limited in terms of the upper limit of the modification rate, but from the viewpoint of reducing the viscosity of the blend after kneading and improving the processability, the modification rate is preferably 98% by mass or less, more preferably 95% by mass or less, and even more preferably 90% by mass or less. In this specification, the "modification ratio" represents the mass ratio of the polymer having a nitrogen atom-containing functional group to the total amount of the hydrogenated diene polymer. The position of introduction of the nitrogen atom into the hydrogenated diene polymer of this embodiment may be any of the polymerization initiation terminal, the molecular chain (including grafts), and the polymerization terminal of the hydrogenated diene polymer.
[0037] When the hydrogenated diene polymer of the present embodiment is produced by polymerizing a conjugated diene monomer and then hydrogenating the polymer, the nitrogen atom is preferably introduced by using a coupling agent containing a nitrogen atom, from the viewpoints of polymerization productivity, a high modification rate, and fuel economy when the polymer is vulcanized.
[0038] As the nitrogen atom-containing coupling agent, from the viewpoints of polymerization productivity and a high modification rate, an isocyanate compound, an isothiocyanate compound, an isocyanuric acid derivative, a nitrogen group-containing carbonyl compound, a nitrogen group-containing vinyl compound, a nitrogen group-containing epoxy compound, a nitrogen group-containing alkoxysilane compound, or the like is preferred. In addition, from the viewpoint of improving the processability when forming a vulcanizate, the number of branches of the coupling agent is preferably large. The number of branches is not particularly limited, but from the viewpoint of suppressing cold flow, 3 branches or more is preferable, and 4 branches or more is more preferable. The upper limit of the number of branches is not particularly limited, but from the viewpoint of productivity, 30 branches or less is preferable. As these nitrogen atom-containing coupling agents, from the viewpoints of polymerization productivity of the hydrogenated diene polymer, a high modification rate, and tensile strength when made into a tire, nitrogen group-containing alkoxysilane compounds are more preferred.
[0039] Examples of the nitrogen group-containing alkoxysilane compound include, but are not limited to, 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silacyclopentane, 2,2-diethoxy-1-(3-triethoxysilylpropyl)-1-aza-2-silacyclopentane, 2,2-dimethoxy-1-(4-trimethoxysilylbutyl)-1-aza-2-silacyclohexane, 2,2-dimethoxy-1-(5-trimethoxysilylpentyl)-1-aza-2-silacycloheptane, 2,2-dimethoxy-1-(3- 2,2-diethoxy-1-(3-diethoxyethylsilylpropyl)-1-aza-2-silacyclopentane, 2-methoxy-2-methyl-1-(3-trimethoxysilylpropyl)-1-aza-2-silacyclopentane, 2-ethoxy-2-ethyl-1-(3-triethoxysilylpropyl)-1-aza-2-silacyclopentane, 2-methoxy-2-methyl-1-(3-dimethoxymethylsilylpropyl)-1-aza-2-silacyclopentane, 2-ethoxy-2-ethyl-1-(3-triethoxysilylpropyl)-1-aza-2-silacyclopentane, 2-methoxy-2-methyl-1-(3-dimethoxymethylsilylpropyl)-1-aza-2-silacyclopentane, 2-ethoxy 2-ethyl-1-(3-diethoxyethylsilylpropyl)-1-aza-2-silacyclopentane, tris(3-trimethoxysilylpropyl)amine, tris(3-methyldimethoxysilylpropyl)amine, tris(3-triethoxysilylpropyl)amine, tris(3-methyldiethoxysilylpropyl)amine, tris(trimethoxysilylmethyl)amine, tris(2-trimethoxysilylethyl)amine, tris(4-trimethoxysilylbutyl)amine, tetrakis[3-(2,2-dimethoxy-1-aza N1-(3-(bis(3-(trimethoxysilyl)propyl)amino)propyl)-N1-methyl-N3-(3-(methyl(3-(trimethoxysilyl)propyl)amino)propyl)-N3-(3-(trimethoxysilyl)propyl)-1,3-propanediamine).
[0040] When the hydrogenated diene polymer of the present embodiment is a copolymer of ethylene and a conjugated diene monomer, it preferably contains a tin atom, a nitrogen atom, or a silicon atom from the viewpoints of fuel economy, abrasion resistance, and flexibility when vulcanized. From the viewpoint of the productivity of the hydrogenated diene polymer, it is preferable to apply a method of introducing a coupling agent containing a tin atom, a nitrogen atom or a silicon atom when the polymerization reaction reaches 100%. Examples of coupling agents containing a tin atom, a nitrogen atom, or a silicon atom include, but are not limited to, tin-containing compounds such as bis(1-octadecylmaleate)dioctyltin, isocyanate compounds such as 4,4-diphenylmethane diisocyanate, and alkoxysilane compounds such as glycidylpropyltrimethoxysilane.
[0041] (Weight average molecular weight) The weight average molecular weight of the hydrogenated diene polymer of the present embodiment is preferably 150,000 or more, and more preferably 200,000 or more, from the viewpoints of shape stability of a molded article of a rubber composition containing the hydrogenated diene polymer, and tensile strength and abrasion resistance of a crosslinked article using the rubber composition. On the other hand, from the viewpoint of processability when the hydrogenated diene polymer of this embodiment is made into a rubber composition for crosslinking, the molecular weight is preferably 1,000,000 or less, more preferably 500,000 or less, and even more preferably 400,000 or less. The molecular weight distribution (=weight average molecular weight / number average molecular weight) of the hydrogenated diene polymer of the present embodiment is preferably 2.0 or less, more preferably 1.8 or less, and even more preferably 1.6 or less, from the viewpoint of fuel economy when the hydrogenated diene polymer of the present embodiment is used in a vulcanizate. On the other hand, from the viewpoint of processability when the hydrogenated diene polymer of this embodiment is made into a rubber composition for crosslinking, the molecular weight distribution of the hydrogenated diene polymer is preferably 1.05 or more, more preferably 1.2 or more, and even more preferably 1.4 or more. The weight average molecular weight and the molecular weight distribution can be calculated from the polystyrene-equivalent molecular weight measured by GPC (gel permeation chromatography).
[0042] (Additives) The hydrogenated diene polymer of the present embodiment may contain additives such as a deactivator and a neutralizer added thereto at the end of the polymerization process, if necessary. Examples of the quenching agent include, but are not limited to, water; alcohols such as methanol, ethanol, and isopropanol; and the like. The final stage of the polymerization process refers to a state in which 95% or more of the added monomer has been consumed in the polymerization. Examples of neutralizing agents include, but are not limited to, carboxylic acids such as stearic acid, oleic acid, and versatic acid (a highly branched carboxylic acid mixture having 9 to 11 carbon atoms, with the majority having 10 carbon atoms); aqueous solutions of inorganic acids, and carbon dioxide gas. It is also preferable to add a rubber stabilizer at the final stage of the polymerization process of the hydrogenated diene polymer from the viewpoints of preventing gel formation and improving processing stability. Examples of rubber stabilizers include, but are not limited to, antioxidants such as 2,6-di-tert-butyl-4-hydroxytoluene (hereinafter also referred to as "BHT"), n-octadecyl-3-(4'-hydroxy-3',5'-di-tert-butylphenol)propionate, and 2-methyl-4,6-bis[(octylthio)methyl]phenol.
[0043] Furthermore, in order to improve the productivity of the polymer and the processability when an inorganic filler or the like is blended during tire production, a rubber softener may be added as necessary, for example, at the final stage of the polymerization process of the hydrogenated diene polymer. The rubber softener is not particularly limited, but examples thereof include extender oil, liquid rubber, resin, etc. From the viewpoints of processability, productivity, and economic efficiency, extender oil is preferred. The method of adding the rubber softener to the hydrogenated diene polymer of the present embodiment is not limited to the following, but a preferred method is to add the rubber softener to a polymer solution, mix, and remove the solvent from the resulting polymer solution containing the rubber softener. Preferable extender oils include, for example, aromatic oils, naphthenic oils, paraffinic oils, etc. Among these, from the viewpoint of environmental safety, prevention of oil bleeding, and wet skid resistance, aromatic substitute oils having a polycyclic aromatic (PCA) content of 3 mass% or less according to the IP346 method are preferable. Examples of aroma substitute oils include Treated Distillate Aromatic Extracts (TDAE) and Mild Extraction Solvate (MES) as shown in Kautschuk Gummi Kunststoffe 52(12)799(1999), as well as Residual Aromatic Extracts (RAE). The content of the extender oil in the rubber composition using the hydrogenated diene polymer of this embodiment is preferably 30 mass % or less, more preferably 20 mass % or less, even more preferably 10 mass % or less, and even more preferably 5 mass % or less, from the viewpoint of suppressing deterioration over time when made into a tire. Preferred resins include, but are not limited to, aromatic petroleum resins, coumarone-indene resins, terpene resins, rosin derivatives (including paulownia oil resins), tall oil, tall oil derivatives, rosin ester resins, natural and synthetic terpene resins, aliphatic hydrocarbon resins, aromatic hydrocarbon resins, mixed aliphatic / aromatic hydrocarbon resins, coumarin-indene resins, phenolic resins, p-tert-butylphenol-acetylene resins, phenol-formaldehyde resins, xylene-formaldehyde resins, monoolefin oligomers, diolefin oligomers, hydrogenated aromatic hydrocarbon resins, cyclic aliphatic hydrocarbon resins, hydrogenated hydrocarbon resins, hydrocarbon resins, hydrogenated paulownia oil resins, hydrogenated oil resins, esters of hydrogenated oil resins with monofunctional or polyfunctional alcohols, and the like. These resins may be used alone or in combination of two or more. When hydrogenating, the unsaturated groups may be hydrogenated in their entirety or may be partially left. The effect of adding the resin is to improve the processability of a rubber composition containing the hydrogenated diene polymer and a filler, etc., and to improve the breaking strength of a vulcanizate. The amount of the extender oil, liquid rubber, or resin, etc., added as a rubber softener is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and even more preferably 20 parts by mass or more, based on 100 parts by mass of the hydrogenated diene polymer. By setting the amount added within this range, a rubber composition with excellent abrasion resistance and crack resistance tends to be obtained. In addition, from the viewpoint of improving fuel economy, the amount is preferably 35 parts by mass or less, more preferably 30 parts by mass or less, and even more preferably 25 parts by mass or less.
[0044] A known method can be used to obtain the hydrogenated diene polymer of the present embodiment by removing the solvent from the polymer solution, for example, a method in which the solvent is separated by steam stripping or the like, the hydrogenated diene polymer is filtered, and then dehydrated and dried to obtain the hydrogenated diene polymer, a method in which the polymer is concentrated in a flashing tank and then devolatilized using a vent extruder or the like, and a method in which the polymer is directly devolatilized using a drum dryer or the like.
[0045] (Aluminum content) The hydrogenated diene polymer of the present embodiment preferably has an aluminum content of less than 2 ppm. When the aluminum content is within this range, the hydrogenated diene polymer of the present embodiment tends to be prevented from increasing in viscosity over time. The reason why the hydrogenated diene polymer of the present embodiment can be prevented from increasing in viscosity over time by keeping the aluminum concentration low is described below. That is, when the aluminum content in the hydrogenated diene polymer is 2 ppm or more, the finely dispersed aluminum-containing compound interacts with the heteroatoms of the hydrogenated diene polymer or the residues of the coupling agent, causing an increase in viscosity. Therefore, by keeping the aluminum content below 2 ppm, such an increase in viscosity can be suppressed. In particular, when the hydrogenated diene polymer contains nitrogen atoms, and further, the nitrogen atoms are likely to become primary amines, and further, when the hydrogenated diene polymer contains a coupling agent having an alkoxysilane, the effect of suppressing the increase in viscosity over time is remarkable by having an aluminum content of less than 2 ppm. The aluminum content of the hydrogenated diene polymer can be measured by the method described in the Examples below, and can be controlled to be within the above-mentioned numerical range by adjusting the type and amount of the polymerization catalyst or hydrogenation catalyst, deashing, or the conditions of the solvent removal step described below.
[0046] [Method for producing hydrogenated diene polymer] The hydrogenated diene polymer of the present embodiment can be produced through a polymerization step, a modification step, and a hydrogenation step.
[0047] (Polymerization process) The polymerization method in the polymerization step is not particularly limited, and any of solution polymerization, gas phase polymerization, and bulk polymerization can be used. From the viewpoint of commercial production, however, solution polymerization is particularly preferred. In addition, the polymerization method is preferably a batch method in this embodiment, from the viewpoint of suppressing side reactions and making it easy to control the molecular structure. When a solution polymerization method is used, the monomer concentration in the solution is preferably 5% by mass or more, more preferably 10% by mass or more. When the monomer concentration in the solution is 5% by mass or more, the amount of the obtained polymer is sufficient, which is preferable from the viewpoint of cost. In addition, the monomer concentration in the solution is preferably 50% by mass or less, more preferably 30% by mass or less. When the monomer concentration in the solution is 50% by mass or less, the solution viscosity can be prevented from becoming too high, stirring is easily performed, and the polymerization process tends to be easily carried out.
[0048] <Polymerization initiator> When anionic polymerization is carried out in the polymerization step, the polymerization initiator is not particularly limited, but an organolithium compound is preferably used. The organic lithium compound is preferably one having an alkyl group having 2 to 20 carbon atoms, and examples thereof include, but are not limited to, ethyl lithium, n-propyl lithium, isopropyl lithium, n-butyl lithium, sec-butyl lithium, tert-butyl lithium, tert-octyl lithium, n-decyl lithium, phenyl lithium, 2-naphthyl lithium, 2-butyl-phenyl lithium, 4-phenyl-butyl lithium, cyclohexyl lithium, cyclopentyl lithium, a reaction product of diisopropenylbenzene and butyl lithium, etc. Among these, n-butyl lithium and sec-butyl lithium are preferred from the viewpoints of availability, safety, etc. When coordination polymerization is performed in the polymerization step, it is preferable to use, for example, the polymerization catalyst composition described in JP-A-2020-45500 as the polymerization initiator.
[0049] <Polymerization method> The method for producing a diene polymer by anionic polymerization or coordination polymerization of a predetermined monomer using a polymerization initiator is not particularly limited, and any conventionally known method can be used. Specifically, in an organic solvent inert to the reaction, for example, a hydrocarbon solvent such as an aliphatic, alicyclic, or aromatic hydrocarbon compound, 1,3-butadiene, ethylene, or the like is polymerized using, for example, butyllithium as a polymerization initiator, and in the presence of a polar compound as necessary, to obtain the target diene polymer.
[0050] <Hydrocarbon solvents> The hydrocarbon solvent is preferably a hydrocarbon having 3 to 8 carbon atoms, and examples thereof include, but are not limited to, propane, n-butane, isobutane, n-pentane, isopentane, n-hexane, cyclohexane, propene, 1-butene, isobutene, trans-2-butene, cis-2-butene, 1-pentene, 2-pentene, 1-hexene, 2-hexene, benzene, toluene, xylene, and ethylbenzene. These may be used alone or in combination of two or more.
[0051] <Polar Compounds in Anionic Polymerization> In the polymerization step, a polar compound may be added. Polar compounds are compounds used to control the microstructure of conjugated diene moieties in polymers, such as compounds that increase the 1,2-bonds in butadiene and the 3,4-bonds in isoprene. The polar compound is not particularly limited, and any of the known compounds that have been generally used as conventional polar compounds can be used. Examples of the polar compound include, but are not limited to, ethers and tertiary amines such as dimethoxybenzene, tetrahydrofuran, dimethoxyethane, diethylene glycol dibutyl ether, diethylene glycol dimethyl ether, 2,2-di(2-tetrahydrofuryl)propane, triethylamine, pyridine, N-methylmorpholine, N,N,N',N'-tetramethylethylenediamine, and 1,2-dipiperidinoethane. Potassium salts such as potassium t-amylate and potassium t-butoxide, and sodium salts such as sodium t-amylate can also be used. These polar compounds may be used alone or in combination of two or more.
[0052] The amount of the polar compound used is preferably 0.01 molar equivalents or more, more preferably 0.05 molar equivalents or more, per mole of the organolithium compound as the polymerization initiator. The polar compound is also called a vinylating agent, and by setting the amount of the polar compound used to 0.01 molar equivalents or more, the effect of addition is obtained, and the 1,2-bonds tend to be easily increased. For example, adding 0.1 molar equivalents per mole of the organolithium compound can improve the 1,2-bonds by about 2%. The amount of the polar compound used as the vinylating agent is preferably 1000 molar equivalents or less, more preferably 500 molar equivalents or less, per mole of the organolithium compound. By setting the amount of the polar compound used to 1000 molar equivalents or less, the reaction rate of the monomer can be prevented from changing significantly, and the polymerization reaction tends to be controlled.
[0053] <Reaction temperature> The reaction temperature during polymerization is not particularly limited as long as the reaction proceeds favorably, but is preferably from -10°C to 100°C, more preferably from 25°C to 70°C.
[0054] (Denaturation process) By reacting the active terminal of the diene polymer obtained by the above-mentioned polymerization step with a compound having a functional group that interacts with silica, a functional group that interacts with silica can be introduced into the polymerization end terminal of the diene polymer, thereby obtaining a diene polymer with a modified polymerization end terminal. The diene polymer used in the modification reaction (hereinafter also referred to as terminal modification reaction) may be one whose polymerization initiation terminal is unmodified or modified, so long as it has an active terminal. The compound used in the modification step is not particularly limited as long as it has a functional group that interacts with silica and can react with the active terminal of the polymer. For example, it is preferable to use a terminal modifier containing a tin atom or a nitrogen atom, and it is more preferable to use a terminal modifier containing a nitrogen atom.
[0055] The modification step also includes a coupling step which involves an increase in molecular weight. Specifically, a random diene polymer having a branched structure can be obtained by reacting the active terminal of a polymer with a coupling agent having a plurality of reaction sites. The nitrogen-containing coupling agent is called a modifier, and by selecting a compound having a coupling function as the modifier, a coupling effect can be obtained by the modification step.
[0056] In a modification reaction accompanied by an increase in molecular weight, the modification rate (coupling rate) affects the molecular weight distribution of the modified polymer. Therefore, from the viewpoint of controlling the molecular weight distribution to 1.75 or less, the modification rate is preferably 65% by mass or more, more preferably 70% by mass or more, and even more preferably 75% by mass or more.
[0057] When the modification step is carried out using a modifying agent having multiple functional groups, a hyperbranched polymer is produced by a coupling reaction. Regardless of the number of functional groups, if the modification rate is high, the molecular weight distribution tends to shift while maintaining its sharpness. Since the structure of the modifier has little effect on the molecular weight distribution, it is possible to select the modifier depending on the functions expected of the modified diene polymer to be produced. The modification rate can be measured by the method described in the Examples below.
[0058] As the nitrogen atom-containing terminal modifying agent, from the viewpoints of polymerization productivity and a high modification rate, preferred examples thereof include isocyanate compounds, isothiocyanate compounds, isocyanuric acid derivatives, nitrogen group-containing carbonyl compounds, nitrogen group-containing vinyl compounds, nitrogen group-containing epoxy compounds, and nitrogen group-containing alkoxysilane compounds. As these nitrogen atom-containing terminal modifiers, nitrogen group-containing alkoxysilane compounds are more preferred from the viewpoints of polymerization productivity, high modification rate, and tensile strength when made into a tire. Examples of the nitrogen atom-containing alkoxysilane compound include, but are not limited to, 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silacyclopentane, 2,2-diethoxy-1-(3-triethoxysilylpropyl)-1-aza-2-silacyclopentane, 2,2-dimethoxy-1-(4-trimethoxysilylbutyl)-1-aza-2-silacyclohexane, 2,2-dimethoxy-1-(5-trimethoxysilylpentyl)-1-aza-2-silacycloheptane, 2,2-dimethoxy-1-(3 -dimethoxymethylsilylpropyl)-1-aza-2-silacyclopentane, 2,2-diethoxy-1-(3-diethoxyethylsilylpropyl)-1-aza-2-silacyclopentane, 2-methoxy-2-methyl-1-(3-trimethoxysilylpropyl)-1-aza-2-silacyclopentane, 2-ethoxy-2-ethyl-1-(3-triethoxysilylpropyl)-1-aza-2-silacyclopentane, 2-methoxy-2-methyl-1-(3-dimethoxymethylsilylpropyl)-1-aza-2-silacyclopentane, and 2- Ethoxy-2-ethyl-1-(3-diethoxyethylsilylpropyl)-1-aza-2-silacyclopentane, tris(3-trimethoxysilylpropyl)amine, tris(3-methyldimethoxysilylpropyl)amine, tris(3-triethoxysilylpropyl)amine, tris(3-methyldiethoxysilylpropyl)amine, tris(trimethoxysilylmethyl)amine, tris(2-trimethoxysilylethyl)amine, and tris(4-trimethoxysilylbutyl)amine, tetrakis[3-(2,2-dimethoxy-1- aza-2-silacyclopentane)propyl]-1,3-propanediamine, tetrakis(3-trimethoxysilylpropyl)-1,3-propanediamine, tetrakis(3-trimethoxysilylpropyl)-1,3-propanediamine, tetrakis(3-trimethoxysilylpropyl)-1,3-bisaminomethylcyclohexane, and N1-(3-(bis(3-(trimethoxysilyl)propyl)amino)propyl)-N1-methyl-N3-(3-(methyl(3-(trimethoxysilyl)propyl)amino)propyl)-N3-(3-(trimethoxysilyl)propyl)-1,3-propanediamine.
[0059] The terminal modification reaction of the polymer can be carried out, for example, as a solution reaction. This solution reaction may be carried out using a solution containing unreacted monomers after the polymerization reaction in the polymerization step, or may be carried out after isolating the polymer contained in the solution and dissolving it in a suitable solvent such as cyclohexane. In addition, when the polymerization method is a continuous method, the terminal modification reaction is also preferably a continuous method. The method of adding the terminal modifying agent is not particularly limited, and examples thereof include a method of adding the agent all at once, a method of adding the agent in portions, and a method of adding the agent continuously.
[0060] The amount of the compound used in the terminal modification reaction may be appropriately set depending on the type of compound used in the reaction, but is preferably 0.1 molar equivalent or more, more preferably 0.3 molar equivalent or more, relative to 1 mole of the metal atom involved in the polymerization reaction contained in the polymerization initiator. By setting the amount to 0.1 molar equivalent or more, the modification reaction can be sufficiently progressed, and the dispersibility of silica can be suitably improved in a rubber composition containing the modified polymer and silica.
[0061] The temperature of the terminal modification reaction is usually the same as the temperature of the polymerization reaction, and is preferably −20 to 150° C., more preferably 0 to 120° C., and further preferably 20 to 100° C. If the temperature of the modification reaction is low, the viscosity of the modified polymer tends to increase. On the other hand, if the temperature of the modification reaction is high, the polymerization active terminals are likely to be deactivated. The reaction time of the modification reaction is preferably 1 minute to 5 hours, and more preferably 2 minutes to 1 hour.
[0062] (Reaction termination step) When anionic polymerization is carried out in the polymerization step, the polymerization reaction can be terminated by adding a known reaction terminator. Examples of the reaction terminator include, but are not limited to, alcohols such as methanol, ethanol, and isopropanol; polar solvents having active protons such as acetic acid; and mixtures thereof, or mixtures of the polar solvents with non-polar solvents such as hexane and cyclohexane. The amount of the reaction terminator added is usually preferably about the same molar amount or about twice the molar amount of the anionic polymerization initiator.
[0063] (Hydrogenation process) In the method for producing the hydrogenated diene polymer of this embodiment, the hydrogenation method and reaction conditions are not particularly limited, and hydrogenation may be carried out by a known method under known conditions. The reaction is usually carried out at 20 to 150° C. under a hydrogen pressure of 0.1 to 10 MPa in the presence of a hydrogenation catalyst. The hydrogenation rate can be controlled by adjusting the amount of hydrogenation catalyst, the hydrogen pressure during the hydrogenation reaction, the reaction time, etc.
[0064] As the hydrogenation catalyst, a compound containing any of metals in Groups 4 to 11 of the Periodic Table of Elements can usually be used. Such compounds are not limited to the following, but for example, compounds containing Ti, V, Co, Ni, Zr, Ru, Rh, Pd, Hf, Re, and Pt atoms can be used as the hydrogenation catalyst. More specifically, metallocene compounds such as Ti, Zr, Hf, Co, Ni, Pd, Pt, Ru, Rh, and Re; supported heterogeneous catalysts in which metals such as Pd, Ni, Pt, Rh, and Ru are supported on a support such as carbon, silica, alumina, and diatomaceous earth; homogeneous Ziegler-type catalysts in which an organic salt or acetylacetone salt of a metal element such as Ni or Co is combined with a reducing agent such as organoaluminum; organometallic compounds or complexes such as Ru and Rh; and fullerenes and carbon nanotubes in which hydrogen is absorbed. Among these, metallocene compounds containing any one of Ti, Zr, Hf, Co, and Ni are preferred from the viewpoint of being capable of carrying out a hydrogenation reaction in a homogeneous system in an inert organic solvent, and metallocene compounds containing any one of Ti, Zr, and Hf are more preferred. The hydrogenation catalyst may be used alone or in combination of two or more kinds.
[0065] A preferred method for producing the hydrogenated diene polymer of this embodiment is to carry out solution polymerization, and then subject the resulting polymer solution as is to a modification step as necessary, and then to a hydrogenation step as necessary. The hydrogenated diene polymer of the present embodiment can be obtained by removing the solvent from the polymer solution obtained above and isolating the polymer. Examples of the method for isolating the polymer include a known method for removing the solvent such as steam stripping, and a method for isolating the polymer by a drying operation such as heat treatment using a dehydrating extruder, a drying extruder, or a conveyer.
[0066] [Veil] The veil of this embodiment is produced by molding the hydrogenated diene polymer of this embodiment described above. A veil is a block-shaped compact, measuring 1000cm 3 The above molded article is preferable. Furthermore, it is more preferable that the molded article is a rectangular parallelepiped bale weighing 17.5 kg to 35 kg. The molding compression pressure for the molded product is preferably 3 to 30 MPa, more preferably 10 to 20 MPa. When the molding compression pressure is 30 MPa or less, the device can be designed compactly and the installation efficiency is good, and when the molding compression pressure is 3 MPa or more, the moldability is good. The temperature of the hydrogenated diene polymer during molding is preferably 30 to 120°C, and more preferably 50 to 100°C from the viewpoints of reducing residual solvent and suppressing thermal degradation. If the temperature of the hydrogenated diene polymer during molding is 30° C. or higher, moldability is good, while if the temperature is 120° C. or lower, gel formation due to thermal degradation of the rubber composition is suppressed, which is preferable. The higher the temperature and pressure during molding, the smaller the specific surface area of the bale. The pressure retention time during compression is preferably 3 to 30 seconds, more preferably 5 to 20 seconds. When the pressure retention time during compression is 30 seconds or less, production efficiency is good, and when it is 5 seconds or more, moldability is good. In order to prevent the molded bodies from sticking to each other, it is preferable to wrap them in a resin film (wrapping sheet). The type of resin that can be used for the film includes, for example, polyethylene, ethylene copolymer resin, polystyrene, high impact polystyrene, and PET. From the viewpoints of ease of handling during transportation of the molded article and preventing condensation from forming in the gap between the packaging sheet and the bale, it is preferable that the packaging sheet has good adhesion.
[0067] [Rubber composition] The rubber composition of the present embodiment contains 100 parts by mass of a rubber component containing the hydrogenated diene polymer of the present embodiment described above and other diene-based rubbers, and 20 parts by mass or more and 100 parts by mass or less of a silica-based inorganic filler. The amount of the hydrogenated diene polymer of this embodiment per 100 parts by mass of the rubber component is preferably 10 parts by mass or more, more preferably 20 parts by mass or more, and even more preferably 30 parts by mass or more. By setting the amount of hydrogenated diene polymer in the rubber component within the above range, the breaking strength of the vulcanized product tends to be excellent. Also, from the viewpoint of excellent processability when vulcanized, the amount is preferably 50 parts by mass or less, more preferably 45 parts by mass or less, and even more preferably 40 parts by mass or less. The rubber composition of the present embodiment preferably contains a diene rubber other than the hydrogenated diene polymer of the present embodiment. Examples of such diene polymers include, but are not limited to, conjugated diene polymers or hydrogenated products thereof, random copolymers of conjugated diene compounds and vinyl aromatic compounds or hydrogenated products thereof, block copolymers of conjugated diene compounds and vinyl aromatic compounds or hydrogenated products thereof, non-diene polymers, and natural rubber. Specific examples include, but are not limited to, styrene-based elastomers such as butadiene rubber or a hydrogenated product thereof, isoprene rubber or a hydrogenated product thereof, styrene-butadiene rubber or a hydrogenated product thereof, styrene-butadiene block copolymer or a hydrogenated product thereof, and styrene-isoprene block copolymer or a hydrogenated product thereof, and acrylonitrile-butadiene rubber or a hydrogenated product thereof.
[0068] The hydrogenated diene polymer of the present embodiment has a compatibility parameter close to that of natural rubber, and therefore can usually act as a compatibilizer between natural rubber and other rubbers. Specifically, a rubber composition comprising a ternary component of a rubber incompatible with natural rubber, natural rubber, and the hydrogenated diene polymer of the present embodiment can exhibit excellent abrasion resistance and breaking elongation that cannot be achieved without the hydrogenated diene polymer of the present embodiment. The rubber composition is not particularly limited, but may be a rubber composition composed of three components of the hydrogenated diene polymer of the present embodiment, natural rubber, and high-cis-butadiene.
[0069] Examples of natural rubber include, but are not limited to, smoked sheets such as RSS3 to 5, SMR, and epoxidized natural rubber.
[0070] The diene rubber other than the hydrogenated diene polymer of the present embodiment described above may be a modified rubber to which a polar functional group such as a hydroxyl group, an amino group, etc. When used for tires, butadiene rubber, isoprene rubber, styrene-butadiene rubber, natural rubber, and butyl rubber are preferably used.
[0071] The rubber composition of the present embodiment may be used in combination with a non-diene polymer. Examples of non-diene polymers include, but are not limited to, olefin elastomers such as ethylene-propylene rubber, ethylene-propylene-diene rubber, ethylene-butene-diene rubber, ethylene-butene rubber, ethylene-hexene rubber, and ethylene-octene rubber, butyl rubber, brominated butyl rubber, acrylic rubber, fluororubber, silicone rubber, chlorinated polyethylene rubber, epichlorohydrin rubber, α,β-unsaturated nitrile-acrylate-conjugated diene copolymer rubber, urethane rubber, and polysulfide rubber.
[0072] The weight average molecular weight of the diene rubber other than the hydrogenated diene polymer of the present embodiment and the non-diene rubber used in the rubber composition of the present embodiment is preferably 2000 to 2,000,000, more preferably 5000 to 1,500,000, from the viewpoint of the balance between performance and processing characteristics. In addition, low molecular weight diene rubbers and non-diene rubbers, so-called liquid rubbers, can also be used. These diene rubbers and non-diene rubbers may be used alone or in combination of two or more.
[0073] The rubber composition of the present embodiment also contains a silica-based inorganic filler. By dispersing the silica-based inorganic filler in the rubber composition of the present embodiment, the processability when vulcanized tends to be excellent, and the balance between abrasion resistance, breaking strength, and low hysteresis loss and wet skid resistance when vulcanized tends to be excellent. The rubber composition of the present embodiment contains a silica-based inorganic filler, and therefore can be suitably used for vulcanized rubber applications such as tires, automobile parts such as anti-vibration rubber, and shoes.
[0074] The content of the silica-based inorganic filler in the rubber composition of this embodiment is 20 parts by mass or more, preferably 50 parts by mass or more, more preferably 60 parts by mass or more, and even more preferably 70 parts by mass or more, per 100 parts by mass of the rubber component containing the hydrogenated diene polymer of this embodiment and other diene-based rubbers, from the viewpoint of excellent abrasion resistance and fracture strength when vulcanized. Furthermore, from the viewpoint of achieving an excellent balance between processability when made into a vulcanizate and low hysteresis loss and wet skid resistance when made into a vulcanizate, the amount is 100 parts by mass or less, preferably 90 parts by mass or less, more preferably 85 parts by mass or less, and even more preferably 80 parts by mass or less.
[0075] The silica-based inorganic filler is not particularly limited and any known filler can be used, but solid particles containing SiO2 or Si3Al as a constituent unit are preferred, and solid particles containing SiO2 or Si3Al as the main component of the constituent unit are more preferred. Here, the main component refers to a component contained in the silica-based inorganic filler in an amount of 50% by mass or more, preferably 70% by mass or more, and more preferably 80% by mass or more.
[0076] Specific silica-based inorganic fillers include, but are not limited to, inorganic fibrous materials such as silica, clay, talc, mica, diatomaceous earth, wollastonite, montmorillonite, zeolite, and glass fiber. In addition, silica-based inorganic fillers with hydrophobic surfaces and mixtures of silica-based inorganic fillers and inorganic fillers other than silica-based fillers are also included. Among these, silica and glass fiber are preferred from the viewpoint of strength and abrasion resistance, and silica is more preferred. Examples of silica include dry silica, wet silica, and synthetic silicate silica. Among these silicas, wet silica is preferred from the viewpoint of excellent balance between the effect of improving fracture strength and wet skid resistance.
[0077] In order to obtain practically good abrasion resistance and breaking strength in the rubber composition of this embodiment, the nitrogen adsorption specific surface area of the silica-based inorganic filler determined by the BET adsorption method is 100 m 2 / g or more 300m 2 / g or less, and 2 / g or more 250m 2 / g or less. If necessary, the specific surface area is relatively small (for example, the specific surface area is 200 m 2 / g) and silica-based inorganic fillers with a relatively large specific surface area (e.g., 200 m 2 In the rubber composition of the present embodiment, a filler having a relatively large specific surface area (for example, 200 m 2 / g or more), the rubber composition containing the hydrogenated diene polymer of this embodiment is effective in improving the dispersibility of silica, and in particular in improving the abrasion resistance, and tends to achieve a high level of balance between good fracture strength and low hysteresis loss.
[0078] The rubber composition of the present embodiment may contain a filler other than the silica-based inorganic filler. Examples of such fillers include carbon black, metal oxides, and metal hydroxides.
[0079] The carbon black is not limited to the following, but examples thereof include carbon blacks of various classes such as SRF, FEF, HAF, ISAF, and SAF. Among these, carbon blacks having a nitrogen adsorption specific surface area of 50 m 2 / g or more and a dibutyl phthalate (DBP) oil absorption of 80 mL / 100 g or less is preferred. In the rubber composition of the present embodiment, the content of carbon black is preferably 0.5 parts by mass or more and 100 parts by mass or less, more preferably 3.0 parts by mass or more and 100 parts by mass or less, and even more preferably 5.0 parts by mass or more and 50 parts by mass or less, per 100 parts by mass of the rubber component containing the hydrogenated diene polymer of the present embodiment. In the rubber composition of the present embodiment, the content of carbon black is preferably 0.5 parts by mass or more per 100 parts by mass of the rubber component from the viewpoint of expressing performance required for applications such as tires, such as dry grip performance and electrical conductivity, and is preferably 100 parts by mass or less per 100 parts by mass of the rubber component from the viewpoint of dispersibility.
[0080] Metal oxide refers to solid particles whose main component is a structural unit represented by the chemical formula MxOy (M represents a metal atom, and x and y each independently represent an integer of 1 to 6). Examples of metal oxides include, but are not limited to, alumina, titanium oxide, magnesium oxide, and zinc oxide. Examples of metal hydroxides include, but are not limited to, aluminum hydroxide, magnesium hydroxide, and zirconium hydroxide.
[0081] The rubber composition of the present embodiment may contain a silane coupling agent. The silane coupling agent has a function of strengthening the interaction between the rubber component and the inorganic filler, and has a group having affinity or binding properties for each of the rubber component and the silica-based inorganic filler. A compound having a sulfur bond portion and an alkoxysilyl group or a silanol group portion in one molecule is preferable. Examples of such compounds include, but are not limited to, bis-[3-(triethoxysilyl)-propyl]-tetrasulfide, bis-[3-(triethoxysilyl)-propyl]-disulfide, and bis-[2-(triethoxysilyl)-ethyl]-tetrasulfide. In the rubber composition of the present embodiment, the content of the silane coupling agent is preferably 0.1 parts by mass or more and 30 parts by mass or less, more preferably 0.5 parts by mass or more and 20 parts by mass or less, and even more preferably 1.0 parts by mass or more and 15 parts by mass or less, relative to 100 parts by mass of the silica-based inorganic filler. When the content of the silane coupling agent is within the above range, the above-mentioned effect of the addition of the silane coupling agent tends to be more remarkable.
[0082] The rubber composition of the present embodiment may contain a rubber softener from the viewpoint of improving its processability. The amount of rubber softener added is expressed as the total amount including the amount of rubber softener already contained in the above-mentioned hydrogenated diene polymer or other diene-based rubber, and the amount of rubber softener added when preparing the rubber composition, per 100 parts by mass of the rubber component containing the hydrogenated diene polymer of the present embodiment described above.
[0083] Suitable rubber softeners include extender oils, liquid rubbers, and resins. Mineral oil-based rubber softeners known as process oils or extender oils, which are used to soften rubber, increase its volume, and improve its processability, are mixtures of aromatic rings, naphthenic rings, and paraffin chains; those in which the carbon number of paraffin chains accounts for 50% or more of the total carbon are called paraffinic; those in which the carbon number of naphthenic rings accounts for 30% to 45% of the total carbon are called naphthenic; and those in which the aromatic carbon number accounts for more than 30% of the total carbon are called aromatic. In the rubber composition of the present embodiment, the content of the rubber softener is preferably 0 to 100 parts by mass, more preferably 10 to 90 parts by mass, and even more preferably 30 to 90 parts by mass, per 100 parts by mass of the rubber component. By making the content of the rubber softener 100 parts by mass or less per 100 parts by mass of the rubber component, bleeding out is suppressed, and stickiness of the surface of the rubber composition tends to be suppressed.
[0084] From the viewpoint of improving low-temperature performance, the rubber composition of the present embodiment preferably contains a liquid rubber. Examples of the liquid rubber include liquid butadiene rubber, liquid styrene butadiene rubber, liquid isoprene rubber, etc. These liquid rubbers may be used alone or in combination of two or more. By adding the liquid rubber, the rubber composition of the present embodiment tends to have a lower elastic modulus at low temperatures and excellent low-temperature performance. In addition, the liquid rubber selected from the above has an unsaturated bond in the molecule, and therefore tends to bond with the rubber component when the rubber composition is vulcanized, thereby increasing the breaking strength.
[0085] The molecular weight of the liquid rubber is preferably 1000 or more, more preferably 1500 or more. By setting the molecular weight within the above range, the number of entanglements of the molecular chains constituting the liquid rubber increases, and the breaking strength tends to be excellent. In addition, the molecular weight of the liquid rubber is preferably 10000 or less, more preferably 9000 or less. By setting the molecular weight within this range, the viscosity is reduced, and the processability when making into a vulcanizate is excellent.
[0086] The amount of liquid rubber added in the rubber composition of the present embodiment is preferably 2 parts by mass or more, more preferably 5 parts by mass or more, and even more preferably 10 parts by mass or more, based on 100 parts by mass of the rubber component containing the hydrogenated diene polymer of the present embodiment. By setting the amount added within this range, the rubber composition tends to have a lower elastic modulus at low temperatures and excellent low-temperature performance. In addition, from the viewpoint of improving the wear resistance of the rubber composition, the amount is preferably 25 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 15 parts by mass or less. If the content of the liquid rubber is too high, the rubber composition becomes soft and the wear resistance is reduced, but by setting the amount within this range, the hardness of the rubber composition when vulcanized is improved, and the wear resistance tends to be improved.
[0087] The rubber composition can be prepared by mixing the hydrogenated diene polymer of this embodiment, other diene-based rubbers, a silica-based inorganic filler, and, if necessary, additives such as carbon black or other fillers, a silane coupling agent, and a rubber softener. Methods for preparing the rubber composition include, but are not limited to, a melt-kneading method using a general mixer such as an open roll, a Banbury mixer, a kneader, a single-screw extruder, a twin-screw extruder, or a multi-screw extruder, and a method in which the components are dissolved and mixed and then the solvent is removed by heating. Among these, the melt kneading method using a roll, a Banbury mixer, a kneader, or an extruder is preferred from the viewpoints of productivity and good kneading properties. In addition, either a method of kneading the rubber component, other fillers, a silane coupling agent, and additives all at once or a method of mixing them in several batches can be applied.
[0088] The rubber composition of the present embodiment may be a vulcanized composition that has been subjected to a vulcanization treatment with a vulcanizing agent. Examples of the vulcanizing agent include, but are not limited to, radical generators such as organic peroxides and azo compounds, oxime compounds, nitroso compounds, polyamine compounds, sulfur, and sulfur compounds. Examples of the sulfur compounds include sulfur monochloride, sulfur dichloride, disulfide compounds, and polymeric polysulfur compounds. In the rubber composition of the present embodiment, the content of the vulcanizing agent is preferably 0.01 parts by mass to 20 parts by mass, more preferably 0.1 parts by mass to 15 parts by mass, based on 100 parts by mass of the rubber component. As the vulcanization method, a conventionally known method can be applied, and the vulcanization temperature is preferably 120°C to 200°C, more preferably 140°C to 180°C.
[0089] In vulcanization, a vulcanization accelerator may be used as necessary. As the vulcanization accelerator, a conventionally known material can be used, and examples thereof include, but are not limited to, sulfenamide-based, guanidine-based, thiuram-based, aldehyde-amine-based, aldehyde-ammonia-based, thiazole-based, thiourea-based, and dithiocarbamate-based vulcanization accelerators. Furthermore, the vulcanization aid may include, but is not limited to, zinc oxide and stearic acid. The content of the vulcanization accelerator is preferably 0.01 parts by mass or more and 20 parts by mass or less, and more preferably 0.1 parts by mass or more and 15 parts by mass or less, based on 100 parts by mass of the rubber component containing the hydrogenated diene polymer of the present embodiment.
[0090] In the rubber composition of the present embodiment, various additives such as softeners and fillers other than those described above, heat stabilizers, antistatic agents, weather stabilizers, antioxidants, colorants, and lubricants may be used within the scope that does not impair the object of the present embodiment. As the other softening agent, a known softening agent can be used. As the other filler, there is no particular limitation, but examples thereof include calcium carbonate, magnesium carbonate, aluminum sulfate, and barium sulfate. As the heat resistance stabilizer, antistatic agent, weather resistance stabilizer, antiaging agent, colorant, and lubricant, known materials can be used.
[0091] 〔tire〕 The rubber composition of the present embodiment is suitably used as a rubber composition for tires. That is, the tire of the present embodiment is an article molded from the rubber composition. The rubber composition for tires is not limited to the following, but can be used in various parts of tires such as fuel-efficient tires, all-season tires, high-performance tires, studless tires, etc., such as treads, carcasses, sidewalls, beads, etc. In particular, the rubber composition for tires has an excellent balance between abrasion resistance, breaking strength, low hysteresis loss, and wet skid resistance when vulcanized, and is therefore suitably used for the treads of fuel-efficient tires and high-performance tires. EXAMPLES
[0092] Hereinafter, the present embodiment will be described in more detail with reference to specific examples and comparative examples, but the present invention is not limited to the following examples and comparative examples. Various physical properties in the examples and comparative examples were measured by the methods shown below.
[0093] [Methods for measuring physical properties] (Weight average molecular weight (Mw) of hydrogenated diene polymer) The hydrogenated diene polymers produced in the Examples and Comparative Examples described below were used as measurement samples, and a chromatogram was measured using a GPC measurement device in which three columns packed with polystyrene-based gel were connected, and the weight average molecular weight (Mw) was calculated based on a calibration curve using standard polystyrene. The specific measurement conditions are as follows. 20 μL of the measurement solution described below was injected into the GPC measurement device and the measurement was carried out. <Measurement conditions> Equipment: Tosoh Corporation product name "HLC-8320GPC" Eluent: 5mmol / L triethylamine in tetrahydrofuran (THF) Guard column: Tosoh Corporation's product name "TSKguardcolumn SuperH-H" Separation column: Tosoh Corporation product names "TSKgel SuperH5000", "TSKgel SuperH6000", and "TSKgel SuperH7000" connected in this order. Oven temperature: 40℃ Flow rate: 0.6mL / min Detector: RI detector (Tosoh Corporation product name "HLC8020") Measurement solution: 10 mg of sample dissolved in 20 mL of THF
[0094] (Mooney Viscosity of Hydrogenated Diene Polymer and Rubber Composition) The hydrogenated diene polymers and rubber compositions prepared in the examples and comparative examples described below were used as measurement samples, and the Mooney viscosity was measured using a Mooney viscometer (manufactured by Ueshima Seisakusho Co., Ltd., product name "VR1132") in accordance with ISO 289 using an L-shaped rotor. Specifically, the sample was first preheated at 100°C for 1 minute, then the rotor was rotated at 2 rpm, and the torque was measured after 4 minutes to determine the Mooney viscosity (ML (1+4) ) was decided.
[0095] (Modification rate of hydrogenated diene polymer) The modification rate of the hydrogenated diene polymer was measured by a column adsorption GPC method utilizing the property of the modified hydrogenated diene polymer being adsorbed in a column, as follows. The amount of the sample adsorbed to the silica-based column was measured by subtracting the chromatogram of the sample solution containing the measurement sample and the low molecular weight internal standard polystyrene measured using a column packed with a polystyrene-based gel from the chromatogram of the sample solution measured using a column packed with a silica-based gel, and the modification rate was calculated. The GPC measurement conditions using a polystyrene column are shown below. 20 μL of the measurement solution described below was injected into the GPC measurement device and the measurement was carried out. <GPC measurement conditions using polystyrene columns> Equipment: Tosoh Corporation product name "HLC-8320GPC" Eluent: THF containing 5mmol / L triethylamine Guard column: Tosoh Corporation's product name "TSKguardcolumn SuperH-H" Column: Tosoh Corporation's product names "TSKgel SuperH5000", "TSKgel SuperH6000", and "TSKgel SuperH7000" connected in this order Oven temperature: 40℃ Flow rate: 0.6mL / min Detector: RI detector (Tosoh HLC8020) Measurement solution: 10 mg of sample and 5 mg of standard polystyrene were dissolved in 20 mL of THF to prepare a sample solution. The conditions for GPC measurement using a silica column are shown below. 50 μL of the measurement solution described below was injected into the GPC measurement device and the measurement was carried out. <GPC measurement conditions using silica column> Equipment: Tosoh Corporation product name "HLC-8320GPC" Eluent:THF Guard column: GL Sciences product name "DIOL 4.6 x 12.5 mm 5 micron" Separation column: Agilent Technologies' product names "Zorbax PSM-1000S", "PSM-300S", and "PSM-60S" connected in this order Oven temperature: 40℃, Flow rate: 0.5mL / min Detector: RI detector (Tosoh HLC8020) Calculation method for modification rate: The total peak area of the chromatogram using a polystyrene column was set as 100, the peak area of the sample was set as P1, the peak area of the standard polystyrene was set as P2, the total peak area of the chromatogram using a silica column was set as 100, the peak area of the sample was set as P3, and the peak area of the standard polystyrene was set as P4, and the modification rate (%) was calculated from the following formula. Denaturation rate (%) = [1-(P2 x P3) / (P1 x P4)] x 100 (where P1+P2=P3+P4=100)
[0096] (Hydrogenation rate of hydrogenated diene polymer, formula (S) and formula (X) obtained from the constituent ratios (mol %) of the structural units represented by the formulas (1) to (4), and the amount of bound styrene) 1 The integrated value of the unsaturated bonds in the diene polymer before hydrogenation was obtained by H-NMR measurement. Next, a large amount of methanol was added to the reaction liquid after the hydrogenation reaction to precipitate and recover the hydrogenated diene polymer. Next, the hydrogenated diene polymer was extracted with acetone, and the hydrogenated diene polymer was dried in vacuum. This, 1 Using the sample for H-NMR measurement, the constituent ratios a to d (mol %) of the structural unit represented by the formula (1), the structural unit represented by the formula (2), the structural unit represented by the formula (3), and the structural unit represented by the formula (4) were measured, and the hydrogen conversion rate of the double bond of the structural unit derived from 1,3-butadiene (hereinafter also simply referred to as "hydrogen conversion rate"), the formula (S), and the bound styrene amount were measured. 1 The conditions for H-NMR measurement are as follows. <Measurement conditions> Measuring equipment: JNM-LA400 (JEOL) Solvent: Deuterated chloroform Measurement sample: Samples taken before and after hydrogenation of the polymer Sample concentration: 50mg / mL Observation frequency: 400MHz Chemical shift reference: TMS (tetramethylsilane) Pulse Delay: 2.904 seconds Number of scans: 64 Pulse width: 45° Measurement temperature: 26℃
[0097] (Branching Degree of Hydrogenated Diene Polymer (Bn)) The hydrogenated diene polymers produced in the examples and comparative examples described later were used as samples to measure the branching degree (Bn) by a GPC-light scattering method equipped with a viscosity detector as follows. A gel permeation chromatography (GPC) apparatus (Malvern, product name "GPCmax VE-2001") having three columns packed with polystyrene gel was used to determine the absolute molecular weight of the sample from three detectors connected in that order: a light scattering detector, a refractive index (RI) detector, and a viscosity detector (Malvern, product name "TDA305"), and the intrinsic viscosity of the sample was determined from the results of the RI detector and the viscosity detector. Linear polymer has an intrinsic viscosity [η] = -3.883M 0.771 The shrinkage factor (g') was calculated as the ratio of the intrinsic viscosity corresponding to each molecular weight, where M represents the absolute molecular weight. The obtained shrinkage factor (g') was then used to calculate the branching degree (Bn), defined as g' = 6Bn / {(Bn+1)(Bn+2)}. The eluent used was tetrahydrofuran (hereinafter also referred to as "THF") containing 5 mmol / L triethylamine. The columns used were "TSKgel G4000HXL", "TSKgel G5000HXL", and "TSKgel G6000HXL" manufactured by Tosoh Corporation. 20 mg of the measurement sample was dissolved in 10 mL of THF to prepare a measurement solution, and 100 μL of the measurement solution was injected into a GPC measurement device and measured under conditions of an oven temperature of 40° C. and a THF flow rate of 1 mL / min.
[0098] (Al content of hydrogenated diene polymer) The aluminum content (Al content, unit: ppm) of the hydrogenated diene polymers prepared in the examples and comparative examples described below was measured by elemental analysis using inductively coupled plasma (ICP, Inductive Coupled Plasma, manufactured by Shimadzu Corporation, device name: ICPS-7500).
[0099] [Method of evaluating characteristics] (Evaluation 1: Change in Mooney viscosity of hydrogenated diene polymer over time) The Mooney viscosity of the hydrogenated diene polymers produced in the Examples and Comparative Examples described below was measured under the following conditions. The Mooney viscosity was measured using a Mooney viscometer (manufactured by Ueshima Seisakusho Co., Ltd. under the trade name "VR1132") in accordance with ISO 289 using an L-shaped rotor. The measurement temperature was 100°C. First, the sample was preheated at the test temperature for 1 minute, and then the rotor was rotated at 2 rpm. The torque was measured after 4 minutes to determine the Mooney viscosity (ML (1+4) ) was decided. The difference between the Mooney viscosity measured within 4 hours after the production of the hydrogenated diene polymer and the Mooney viscosity after storage at 25° C. and a humidity of 30% for 1 month was evaluated as ΔML. If ΔML was 0 or more and less than 8, it was marked as ◯, and if it was 8 or more, it was marked as ×. For practical purposes, a ΔML of less than 8 was evaluated as being good.
[0100] (Rating 2: Cold flow) A molded body of 40 mm x 40 mm x thickness (H0) 50 mm was prepared using the hydrogenated diene polymer prepared in the examples and comparative examples described below, and this was used as a measurement sample. A load of 1 kg was applied to this measurement sample at 25°C, and the sample was left for 60 minutes, after which the thickness (H60) was measured. The change rate (%) of the thickness was calculated using the following formula. Thickness change rate (%) = (H0-H60) x 100 / H0 This rate of change in thickness was taken to represent the cold flow, and the result of Example 1 was indexed as 100. The smaller the index, the smaller the cold flow during storage and the better the workability. An index of 80 or more and 89 or less was rated as good (◎ in the table), 90 or more and 99 or less was rated as acceptable for practical use (◯ in the table), 100 or more and 105 or less was rated as slightly poor (△ in the table), and anything over 105 was rated as problematic for practical use (× in the table).
[0101] (Evaluation 3: Veil formability) Using 35 kg of the hydrogenated diene polymers prepared in the Examples and Comparative Examples described below, bales were molded at a molding pressure of 10 MPa and a molding temperature of 80°C. The bale moldability was judged based on the bale size after releasing the compression, according to the following flow. 〇: Bale volume is 40,000 cm 3 More than 50,000cm 3 less than. △: Bale volume is 50,000 cm 3 More than 55,000cm 3 less than. ×: Bale volume is 55,000 cm 3 The end. A bale molded at a given molding temperature and pressure was judged to have excellent bale moldability if its size did not change much before and after the pressure was released. Bales are compressed to a size that allows a specified number to fit into a transport container, so if they expand and are not formed to the specified bale size, the specified number cannot be accommodated, which can easily cause problems during transport. By compressing the bales to the desired size, they can be packed into a container of the specified size for transport, which is advantageous in terms of transportation costs.
[0102] [Method for producing hydrogenated diene polymer] (Preparation of hydrogenation catalyst) In the examples and comparative examples described later, the hydrogenation catalyst used in preparing the hydrogenated diene polymer was prepared by the following method. <Production Example 1> Two liters of dried and purified cyclohexane was charged into a nitrogen-substituted reaction vessel, and 40 millimoles of bis(η5-cyclopentadienyl)titanium di-(p-tolyl) and 150 grams of 1,2-polybutadiene (1,2-vinyl bond content approximately 85%) with a molecular weight of approximately 1,000 were dissolved therein. A cyclohexane solution containing 60 millimoles of n-butyllithium was then added to the reaction vessel and reacted at room temperature for 5 minutes, after which 40 millimoles of n-butanol was immediately added and stirred to obtain a hydrogenation catalyst (TC-1). The resulting hydrogenation catalyst (TC-1) was stored at room temperature. <Production Example 2> A nitrogen-purged reaction vessel was charged with 1 liter of dried and purified cyclohexane, 100 mmol of bis(η5-cyclopentadienyl)titanium dichloride was added, and an n-hexane solution containing 200 mmol of trimethylaluminum was added while thoroughly stirring, and the reaction was carried out at room temperature for about 3 days to obtain a hydrogenation catalyst (TC-2). The obtained hydrogenation catalyst (TC-2) was stored at room temperature.
[0103] (Polymerization of hydrogenated diene polymers) <(Example 1) Hydrogenated diene polymer (sample A)> A 40 L internal volume, temperature-controllable autoclave equipped with an agitator and a jacket was used as a reactor. 2,700 g of 1,3-butadiene and 21,000 g of cyclohexane, from which impurities had been removed in advance, were placed in the reactor, and the internal temperature of the reactor was maintained at 46°C. As a polymerization initiator, 6.0 mmol of n-butyllithium was fed to the reactor. After the polymerization reaction started, the temperature in the reactor began to rise due to heat generated by the polymerization, and the final temperature in the reactor reached 76°C. Two minutes after the reaction temperature reached its peak, 1.5 mmol of 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silacyclopentane (compound 1) was added to the reactor, and a coupling reaction was carried out for 20 minutes. 1.2 mmol of methanol was added to this polymer solution as a reaction terminator, and a diene polymer solution was obtained. Further, the hydrogenation catalyst (TC-1) prepared above was added to the obtained diene polymer solution in an amount of 50 ppm (Ti standard) per 100 parts by mass of the diene polymer, and a hydrogenation reaction was carried out at a hydrogen pressure of 0.8 MPa and an average temperature of 85°C for 1 hour to obtain a hydrogenated diene polymer solution. To the obtained hydrogenated diene polymer solution, 12.6 g of n-octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)-propionate and 3.0 g of 4,6-bis(octylthiomethyl)-o-cresol were added as antioxidants, and the solvent was removed by steam stripping, and the mixture was dried in a dryer to obtain a hydrogenated diene polymer (sample A). The analysis results of sample A are shown in Table 1.
[0104] <(Example 2) Hydrogenated diene polymer (sample B)> A hydrogenated diene polymer (sample B) was obtained in the same manner as in Example 1, except that the amount of the hydrogenation catalyst (TC-1) added was changed to 75 ppm. The results of the analysis of sample B are shown in Table 1.
[0105] <(Example 3) Hydrogenated diene polymer (sample C)> A hydrogenated diene polymer (sample C) was obtained in the same manner as in Example 1, except that the amount of the hydrogenation catalyst (TC-1) added was changed to 90 ppm. The results of the analysis of sample C are shown in Table 1.
[0106] <(Example 4) Hydrogenated diene polymer (sample D)> A hydrogenated diene polymer (sample D) was obtained in the same manner as in Example 2, except that after 1,3-butadiene and cyclohexane were placed in the reactor, 2.0 mmol of tetrahydrofuran (THF) and 4.0 mmol of 2,2-bis(2-oxolanyl)propane (BOP) were placed in the reactor as polar compounds. The analysis results of sample D are shown in Table 1.
[0107] <(Example 5) Hydrogenated diene polymer (sample E)> A hydrogenated diene polymer (sample E) was obtained in the same manner as in Example 2, except that after 1,3-butadiene and cyclohexane were placed in the reactor, 3.0 mmol of tetrahydrofuran (THF) and 5.0 mmol of 2,2-bis(2-oxolanyl)propane (BOP) were placed in the reactor as polar compounds. The analysis results of sample E are shown in Table 1.
[0108] <(Example 6) Hydrogenated diene polymer (sample F)> A hydrogenated diene polymer (sample F) was obtained in the same manner as in Example 2, except that 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silacyclopentane (compound 1) was replaced with tetrakis(3-trimethoxysilylpropyl)-1,3-propanediamine (compound 2) and the amount added was changed to 1.0 mmol. The analysis results of sample F are shown in Table 1.
[0109] <(Example 7) Hydrogenated diene polymer (sample G)> A hydrogenated diene polymer (sample G) was obtained in the same manner as in Example 2, except that 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silacyclopentane (compound 1) was replaced with bis(diethoxymethylsilylpropyl)-N-methylamine (compound 4) and the amount added was changed to 3.0 mmol. The analysis results of sample G are shown in Table 1.
[0110] <( Reference example 8) Hydrogenated diene polymer (sample H) A hydrogenated diene polymer (sample H) was obtained in the same manner as in Example 2, except that 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silacyclopentane (compound 1) was replaced with tetraethoxysilane (compound 5). The analysis results of sample H are shown in Table 1.
[0111] <( Reference example 9) Hydrogenated diene polymer (sample I) A hydrogenated diene polymer (sample I) was obtained in the same manner as in Example 2, except that the amount of 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silacyclopentane (compound 1) added was changed to 1.2 mmol. The analysis results of sample I are shown in Table 1.
[0112] <( Reference example 10) Hydrogenated diene polymer (sample J) A hydrogenated diene polymer (sample J) was obtained in the same manner as in Example 2, except that the amount of 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silacyclopentane (compound 1) added was changed to 0.8 mmol. The analysis results of sample J are shown in Table 1.
[0113] <(Example 11) Hydrogenated diene polymer (sample K)> Except for changing the hydrogenation catalyst to the above-prepared (TC-2), a hydrogenated diene polymer (sample K) was obtained in the same manner as in Example 2. The analysis results of sample K are shown in Table 1.
[0114] <(Example 12) Hydrogenated diene polymer (sample L)> A hydrogenated diene polymer (sample L) was obtained in the same manner as in Example 2, except that the amount of n-butyllithium added was changed to 12.0 mmol, the amount of 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silacyclopentane (compound 1) added was changed to 3.0 mmol, and the amount of ethanol added as a reaction terminator was changed to 2.2 mmol. The analysis results of sample L are shown in Table 1.
[0115] <(Example 13) Hydrogenated diene polymer (sample M)> A hydrogenated diene polymer (sample M) was obtained in the same manner as in Example 2, except that the amount of n-butyllithium added was changed to 3.0 mmol, the amount of 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silacyclopentane (compound 1) added was changed to 0.7 mmol, and the amount of ethanol added as a reaction terminator was changed to 0.5 mmol. The analysis results of sample M are shown in Table 1.
[0116] <(Example 40) Hydrogenated diene polymer (sample T)> A hydrogenated diene polymer (sample T) was obtained in the same manner as in Example 4, except that the amount of 2,2-bis(2-oxolanyl)propane (BOP) added was changed to 5.0 mmol and the amount of hydrogenation catalyst (TC-1) added was changed to 90 ppm. The analysis results of sample T are shown in Table 2.
[0117] <(Example 41) Hydrogenated diene polymer (sample U)> A hydrogenated diene polymer (sample T) was obtained in the same manner as in Example 4, except that the amount of tetrahydrofuran (THF) was changed to 3.0 mmol and the amount of 2,2-bis(2-oxolanyl)propane (BOP) was changed to 5.0 mmol. The analysis results of sample T are shown in Table 2.
[0118] <(Example 42) Hydrogenated diene polymer (sample V)> In the hydrogenation step, the hydrogenation reaction was carried out for 1 hour at a hydrogen pressure of 0.8 MPa and an average temperature of 85° C., and the amount of hydrogen added was changed, so that a hydrogenated diene polymer (sample V) was obtained in the same manner as in Example 40. The analysis results of sample V are shown in Table 2.
[0119] <(Example 43) Hydrogenated diene polymer (sample W)> In the hydrogenation step, the hydrogenation reaction was carried out for 1 hour at a hydrogen pressure of 0.8 MPa and an average temperature of 85° C., and the amount of hydrogen added was changed, but the procedure was the same as in Example 40 to obtain a hydrogenated diene polymer (sample W). The analysis results of sample W are shown in Table 2.
[0120] <(Example 44) Hydrogenated diene polymer (sample X)> A hydrogenated diene polymer (sample X) was obtained in the same manner as in Example 40, except that the amount of tetrahydrofuran (THF) was changed to 3.5 mmol and the amount of 2,2-bis(2-oxolanyl)propane (BOP) was changed to 6.0 mmol. The analysis results of sample X are shown in Table 2.
[0121] <(Example 45) Hydrogenated diene polymer (sample Y)> A hydrogenated diene polymer (sample Y) was obtained in the same manner as in Example 44, except that the amount of hydrogenation catalyst (TC-1) added was changed to 75 ppm. The analysis results of sample Y are shown in Table 2.
[0122] <(Comparative Example 1) Hydrogenated Diene Polymer (Sample N)> Except for changing the amount of hydrogenation catalyst (TC-1) added to 120 ppm, a hydrogenated diene polymer (sample N) was obtained in the same manner as in Example 1. The analysis results of sample N are shown in Table 2.
[0123] <(Comparative Example 2) Hydrogenated Diene Polymer (Sample O)> A hydrogenated diene polymer (sample O) was obtained in the same manner as in Example 1, except that the amount of hydrogenation catalyst (TC-1) added was changed to 40 ppm. The analysis results of sample O are shown in Table 2.
[0124] <(Comparative Example 3) Hydrogenated Diene Polymer (Sample P)> A hydrogenated diene polymer (sample P) was obtained in the same manner as in Example 2, except that after 1,3-butadiene and cyclohexane were placed in the reactor, 5.0 mmol of tetrahydrofuran (THF) and 7.0 mmol of 2,2-bis(2-oxolanyl)propane (BOP) were placed in the reactor as polar compounds. The analysis results of sample P are shown in Table 2.
[0125] <(Comparative Example 4) Hydrogenated Diene Polymer (Sample Q)> A hydrogenated diene polymer (sample Q) was obtained in the same manner as in Example 2, except that 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silacyclopentane (compound 1) was replaced with [N,N-bis(trimethylsilyl)aminopropyl]methyldiethoxysilane (compound 3) and the amount added was changed to 3.0 mmol. The analysis results of sample Q are shown in Table 2.
[0126] <(Comparative Example 5) Hydrogenated Diene Polymer (Sample R)> A hydrogenated diene polymer (sample R) was obtained in the same manner as in Example 2, except that the hydrogenation catalyst was changed to the above-prepared (TC-2), 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silacyclopentane (compound 1) was changed to [N,N-bis(trimethylsilyl)aminopropyl]methyldiethoxysilane (compound 3), and the amount added was changed to 3.0 mmol. The analysis results of sample R are shown in Table 2.
[0127] <(Comparative Example 6) Hydrogenated Diene Polymer (Sample S)> A 40 L internal volume autoclave equipped with an agitator and a jacket and capable of temperature control was used as a reactor, and 2,160 g of 1,3-butadiene, 300 g of styrene, and 21,000 g of cyclohexane, from which impurities had been removed in advance, were placed in the reactor, and 30 mmol of tetrahydrofuran (THF) and 4.9 mmol of 2,2-bis(2-oxolanyl)propane were placed as polar compounds in the reactor, and the internal temperature of the reactor was maintained at 42° C. 33.2 mmol of n-butyllithium was supplied to the reactor as a polymerization initiator. After the polymerization reaction started, the temperature inside the reactor began to rise due to heat generated by the polymerization, and the final temperature inside the reactor reached 76° C. Two minutes after the reaction temperature reached this peak, 6.6 mmol of 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silacyclopentane (compound 1) was added to the reactor, and a coupling reaction was carried out for 20 minutes. To this polymer solution, 6.0 mmol of methanol was added as a reaction terminator to obtain a diene polymer solution. Further, the hydrogenation catalyst (TC-1) prepared above was added to the obtained diene polymer solution in an amount of 50 ppm (Ti standard) per 100 parts by mass of the diene polymer, and a hydrogenation reaction was carried out at a hydrogen pressure of 0.8 MPa and an average temperature of 85°C for 1 hour to obtain a hydrogenated diene polymer solution. To the obtained hydrogenated diene polymer solution, 12.6 g of n-octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)-propionate and 3.0 g of 4,6-bis(octylthiomethyl)-o-cresol were added as antioxidants, and the solvent was removed by steam stripping, and the mixture was dried in a dryer to obtain a hydrogenated conjugated diene polymer (sample S). The analysis results of sample S are shown in Table 2.
[0128] [Table 1]
[0129] [Table 2]
[0130] [Production of rubber composition] (Example 14 to 28, Reference Examples 29 to 31, Examples 32 to 39, 46-51, Comparative Examples 7-16) Rubber compositions were prepared using the hydrogenated diene polymer or hydrogenated diene-based polymer (samples A to P), high-cis polybutadiene (BR, "UBEPOL U150" manufactured by Ube Industries, Ltd.), natural rubber (NR), and styrene-butadiene rubber (SBR, Y031 manufactured by Asahi Kasei Corporation) as rubber components in the formulations shown in Tables 3 to 6 and under the conditions shown below.
[0131] The product names used for each component in Tables 3 to 6 are as follows. Silica (product name "Ultrasil 7000GR" manufactured by Evonik Degussa, nitrogen adsorption specific surface area 170 m 2 / g) Carbon black (product name "Seat KH (N339)" manufactured by Tokai Carbon Co., Ltd.) · S-RAE oil (product name "Process NC140" manufactured by JX Nippon Oil & Energy Corporation) Liquid rubber (Kuraray's product name "Kuraray LBR-302", molecular weight 5500) Silane coupling agent (Evonik Degussa's product name "Si75", bis(triethoxysilylpropyl) disulfide) · Anti-aging agent (N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine) Vulcanization accelerator 1 (N-cyclohexyl-2-benzothiazylsulfinamide) Vulcanization accelerator 2 (diphenyl guanidine)
[0132] The above-mentioned materials were kneaded in the following manner to obtain a rubber composition. Using an enclosed mixer (capacity 0.3 L) equipped with a temperature control device, the first mixing step was carried out by mixing rubber components (hydrogenated diene polymer, hydrogenated diene-based polymer, high-cis polybutadiene, natural rubber, and styrene butadiene rubber), fillers (silica, carbon black), silane coupling agent, S-RAE oil, liquid rubber, zinc oxide, and stearic acid at a filling rate of 60% and a rotor rotation speed of 30 to 50 rpm. At this time, the temperature of the internal mixer was controlled so that the discharge temperature was 155 to 160° C., and each rubber composition (compound) was obtained. Next, in the second stage of kneading, the compound obtained above was cooled to room temperature, and then an antioxidant was added, followed by kneading again to improve the dispersion of the filler. In this case as well, the discharge temperature of the blend was adjusted to 155 to 160°C by controlling the temperature of the mixer. After cooling, the mixture was kneaded in the third stage with an open roll set at 70° C. by adding sulfur and vulcanization accelerators 1 and 2. The mixture was then molded and vulcanized in a vulcanization press at 160° C. for 25 minutes. The properties of the rubber composition before and after vulcanization were evaluated. Specifically, the evaluation was performed by the following methods. The results are shown in Tables 3 to 6.
[0133] (Evaluation of physical properties) <(Evaluation 4) Processability: Compound Mooney Viscosity> The compound obtained above after the second stage kneading and before the third stage kneading was used as a sample, and after preheating at 130°C for 1 minute, the viscosity was measured using a Mooney viscometer in accordance with JIS K6300-1 after rotating the rotor at 2 revolutions per minute for 4 minutes. The result of Comparative Example 8 was set to 100 and indexed. The smaller the index, the better the processability.
[0134] <(Rating 5) Breaking strength> The breaking strength was measured according to the tensile test method of JIS K6251. The results of Comparative Example 8 were indexed with 100 as the index. The larger the index, the better the breaking strength.
[0135] <(Evaluation 6) Abrasion resistance> The amount of wear was measured at 1000 revolutions under a load of 44.4N using an Acron abrasion tester (manufactured by Yasuda Seiki Seisakusho Co., Ltd.) in accordance with JIS K6264-2. The results of Comparative Example 8 were indexed with 100 as the index. The smaller the index, the better the abrasion resistance.
[0136] <(Ratings 7 and 8) Low temperature performance and fuel efficiency: Viscoelastic parameters> Viscoelastic parameters were measured in torsion mode using a viscoelasticity tester "ARES" manufactured by Rheometrics Scientific Co., Ltd. Each measured value was indexed with the result for the rubber composition of Comparative Example 8 set at 100. Tan δ measured at 50°C, a frequency of 10 Hz, and a strain of 3% was used as an index of fuel economy. The smaller the index, the better the fuel economy. The storage modulus (G') measured at -20°C, a frequency of 10 Hz, and a strain of 1% was used as an index of low-temperature performance. The smaller the index, the better the low-temperature performance.
[0137] [Table 3]
[0138] [Table 4]
[0139] [Table 5]
[0140] [Table 6]
[0141] As shown in Tables 4 to 6, it was confirmed that, compared with Comparative Examples 7 to 16, Examples 14 to 39 and 46 to 51 had excellent low-temperature performance and abrasion resistance of the rubber compositions, and further had excellent breaking strength.
[0142] This application is based on a Japanese patent application (Patent Application No. 2020-203168) filed with the Japan Patent Office on December 8, 2020, the contents of which are incorporated herein by reference. [Industrial Applicability]
[0143] The rubber composition according to the present invention has industrial applicability in the fields of tire treads, interior and exterior parts of automobiles, anti-vibration rubber, belts, footwear, foams, various industrial goods, and the like.
Claims
1. The degree of branching (Bn) as measured by a GPC-light scattering measurement method with a viscosity detector is 1.5 or more, When the constituent ratios (mol%) of the structural unit represented by the following formula (1), the structural unit represented by the following formula (2), the structural unit represented by the following formula (3), and the structural unit represented by the following formula (4) are a, b, c, and d, respectively, Satisfying the following formula (S): The hydrogenation rate is 40 to 85%. Contains a nitrogen atom, The modification rate is 70% by mass or more, The content of aromatic vinyl monomer units is 0.1% by mass or less. Hydrogenated diene polymer. Formula (S): 10≦[(a+b) / (a+b+c+d)]×100≦70 【Chemistry 1】
2. The degree of branching (Bn) as measured by a GPC-light scattering measurement method with a viscosity detector is 1.5 or more, Satisfying the following formula (S): The hydrogenation rate is 40 to 80%. The hydrogenated diene polymer according to claim 1. Formula (S): 10≦[(a+b) / (a+b+c+d)]×100≦60
3. The hydrogenated diene polymer according to claim 1 or 2, wherein the following formula (X) is 2.0 or less. Formula (X): (a+c) / (a+b)
4. The hydrogenated diene polymer according to claim 3, wherein the formula (X) is 0.8 or more and 2.0 or less.
5. The hydrogenated diene polymer according to any one of claims 1 to 4, having a hydrogenation rate of 51% or more.
6. The hydrogenated diene polymer according to any one of claims 1 to 5, having a hydrogenation rate of 71% or less.
7. The hydrogenated diene polymer according to any one of claims 1 to 6, having an aluminum content of less than 2 ppm.
8. A veil which is a molded product of the hydrogenated diene polymer according to any one of claims 1 to 7.
9. 100 parts by mass of a rubber component comprising 10 parts by mass or more and 50 parts by mass or less of the hydrogenated diene polymer according to any one of claims 1 to 7 and 50 parts by mass or more and 90 parts by mass or less of a diene rubber; A silica-based inorganic filler is 20 parts by mass or more and 100 parts by mass or less, Contains Rubber composition.
10. The rubber composition according to claim 9 , comprising 2 parts by mass or more and 25 parts by mass or less of the liquid rubber.
11. A tire which is a molded article of the rubber composition according to claim 10.
Citation Information
Patent Citations
Selectively and partially hydrogenated modified polymer composition
JP1996245839A
Rubber composition for cap tread and studless tire with cap tread using the same
JP2008050432A
Method of improving affinity between filler and polymers having a low degree of unsaturation
US8158700B2
Modified polymers and compositions containing the same
WO2003085010A1
Hydrogenated conjugated diene (CO)polymer rubber and method for producing the same
WO2009060931A1